Reported miracles : a critique of Hume - Houston, J. (Joseph) (Cambridge, Cambridge University Press, 1994)
Suppose that one is presented with a report of a miracle as an exception to nature's usual course. Should one believe the report and so come to favour the idea that a god has acted miraculously? David Hume argued that no reasonable person should do anything of the kind. Many religiously skeptical philosophers agree with him, and have both developed and defended his reasoning, while some theologians concur or offer other reasons why those who are believers in God should also refuse to accept accounts of miracles as accurate reportage. This book argues to the contrary. Miracle stories can and may have apologetic value, may contribute towards the reasonableness of belief in God, while appropriately attested miracles may be accepted by believers in God. 'But', it may be insisted, 'scientists and historians, and all of us who want to believe rightly, judiciously, and justifiably, must assume that natural laws always hold, or else epistemic anarchy looms'. Epistemological responses to these worries are forthcoming in this study, and the variously inadequate attitudes of leading twentieth century theologians are repaired where repair is possible. The discussion yields reasons for a fuller integration of theology with the other sciences than is common. These issues have a long history. So the book begins with a careful exposition in their own terms of the views of principal relevant thinkers; this contributes to the history of ideas, as well as presenting essential resources for the argumentative and evaluative study which follows
Augustine on the miraculous -- Aquinas on the miraculous -- Locke on the miraculous-- Bradley and Troeltsch on the miraculous -- The concept of a miracle -- 1, 2 -- Hume's case -- preamble to assessment -- Hume's case tested -- 1, 2 -- Reported miracles and epistemology -- Reported miracles in theology
Includes bibliographical references (pages 258-261) and index
Keywords: Hume, David, -- 1711-1776 -- Religion; Miracles -- History of doctrines; God -- Proof; Epistemology